2002
DOI: 10.1002/jbm.10451
|View full text |Cite
|
Sign up to set email alerts
|

Tissue reaction and biodegradation of implanted cross‐linked high amylose starch in rats

Abstract: The biocompatibility and degradation characteristics of cross-linked high amylose starch (Contramid were investigated in rats over 4 months. Contramid pellets (3-mm diameter and thickness) obtained by direct compression, were implanted subcutaneously and intramuscularly. On sequential time points, macroscopic observations of implantation sites were performed and tissue samples were removed, fixed, and histologically evaluated. No macroscopic inflammatory reaction was observed with Contramid.. Upon histologic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…The present reports showed that starch was a biocompatible and bioabsorbable material. 22,23 The cement with modified starch showed the best antiwashout property among the anti-washout agents used in this study. This may be caused by the modified starch formed viscous gel when gelatinized in water, and physically adsorbed on the surface of the CPC particles, which immobilized the CPC particles and restrain the penetration of liquid into the cement paste.…”
Section: Sodium Alginatementioning
confidence: 97%
“…The present reports showed that starch was a biocompatible and bioabsorbable material. 22,23 The cement with modified starch showed the best antiwashout property among the anti-washout agents used in this study. This may be caused by the modified starch formed viscous gel when gelatinized in water, and physically adsorbed on the surface of the CPC particles, which immobilized the CPC particles and restrain the penetration of liquid into the cement paste.…”
Section: Sodium Alginatementioning
confidence: 97%
“…Starch is a natural polymer which has widespread application ranging from a simple filler or binder [199] to a more functional ingredient in the formulation of capsules [200], coatings [201], subcutaneous implants [202], and tablets. In tablets, starch has been mainly used as a binder, diluents, disintegrant and also as a sustained release agent in matrix systems [203,204].…”
Section: Starch or Starch Based Derivativesmentioning
confidence: 99%
“…It has various practical applications such as a simple binder (76) or as an excipient in the preparation of various formulations including capsules (77), tablets (78), coatings (79) and subcutaneous implants (80). Starch possesses hydrophilic character due to its structure having hydroxyl functional groups.…”
Section: Starch or Starch Based Derivativesmentioning
confidence: 99%